The influence of emotional well-being on wellbeing of healthy people - Shvaiko, Yauhen G. (Journal of the Belarusian State University. Philosophy and Psychology, 2024)
The emotional well-being of a person, which, despite its subjective character, determines his role and participation in public life, is studied. It is suggested that lowering in the emotional background can lead to a reduction in the social activity of an individual and the development of psychosomatic disorders, which, in turn, is fraught with an increased risk of temporary disability and an increased burden on health care. The study takes into account the multidimensional nature of the assessment of subjective well-being, since there is some semantic complexity in the interpretation of the concept of «emotional well-being». Subjective well-being, emotional state, well-being, self-assessment of health, and other aspects of life satisfaction of healthy people (n = 113) surveyed on six methodologies are analysed. It is revealed that there is a correlation between subjective well-being and emotional well-being, satisfaction with the social environment and daily activities, well-being, and self-assessment of health.
Keywords: emotional well-being; psychological well-being; subjective well-being; emotional state; social environment; life satisfaction; well-being; pain; emotional background